Multiply resistant viridans streptococci: susceptibility to beta-lactam antibiotics and comparison of penicillin-binding protein patterns. - Farber, B F (1983)
A unique group of viridans streptococci has been found in South Africa. These organisms were isolated in close temporal and physical proximity to the isolation of penicillin-resistant pneumococci. The strains were resistant to penicillin, oxacillin, the cephalosporins (all generations), piperacillin, azlocillin, and mezlocillin but were susceptible to vancomycin. Penicillin-binding proteins of two penicillin-resistant South African strains of Streptococcus mitis differed markedly from those of two penicillin-susceptible strains but were identical to those seen in a penicillin-resistant strain isolated in Boston. Although both susceptible strains were identified as S. mitis with identical biochemical profiles, their penicillin-binding protein patterns differed from each other. This finding may have significance with regard to the need for additional taxonomic classification of the viridans streptococci.